2004
DOI: 10.1177/1043659603262486
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Meanings, Beliefs, and Practices of Female Circumcision Among Three Nigerian Tribes in the United States and Nigeria

Abstract: The study was conducted to gain insight into the meanings, beliefs, and practices of female circumcision among three Nigerian tribes in the United States and Nigeria. Participant-observations occurred in three sites in Nigeria (Ibadan, Lagos, and Owerri) and in Essex County, New Jersey (Newark, Irvington, and East Orange). A total of 50 informants included adult males and females from the three main Nigerian ethnic tribes: Igbo, Yoruba, and Hausa. Leininger's culture care theory of diversity and universality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 17 publications
(18 reference statements)
1
51
2
Order By: Relevance
“…Female circumcision is an area of abuse of the girl child (Cook, Dickens, & Fathalla, 2003). Contrary to reports of the extensive practice of female circumcision in Africa, the practice is more common in Sierra Leone, Sudan, Egypt, parts of Nigeria, and northern Ghana (Ahlberg, Krantz, Lindmark, & Warsame, 2004; Anuforo, Oyedele, & Pacquaio, 2004). According to Ahlberg and colleagues (2004), female circumcision is considered as a traditional practice and not associated with any religious beliefs.…”
Section: Abuses Of the Girl Childcontrasting
confidence: 58%
See 1 more Smart Citation
“…Female circumcision is an area of abuse of the girl child (Cook, Dickens, & Fathalla, 2003). Contrary to reports of the extensive practice of female circumcision in Africa, the practice is more common in Sierra Leone, Sudan, Egypt, parts of Nigeria, and northern Ghana (Ahlberg, Krantz, Lindmark, & Warsame, 2004; Anuforo, Oyedele, & Pacquaio, 2004). According to Ahlberg and colleagues (2004), female circumcision is considered as a traditional practice and not associated with any religious beliefs.…”
Section: Abuses Of the Girl Childcontrasting
confidence: 58%
“…Moreover, alternative approach would be for healthcare professionals to persuade traditional surgeons to learn basic aseptic techniques or to carry out operations at their local hospital or health centers (Abu Daia, 2000; Magied et al, 2003). It is unacceptable to criticize any social group for this practice without providing constructive alternatives to address cultural beliefs or practices (Anuforo et al, 2004; Nour, 2004). It is only through close collaboration and cooperation, respect for cultural beliefs, and persistent health education programs within those social groups that female circumcision would be discontinued (Nour, 2004).…”
Section: Abuses Of the Girl Childmentioning
confidence: 99%
“…While a range of socioreligious issues foster the practice, to this day a conviction that FGM/C is necessary to control women's sexuality exists in many practicing communities [2, 4]. Studies have also revealed that many members of practicing communities believe that the procedure ensures safe labour [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite mounting opposition, FGC is still practiced for reasons that vary depending on the culture in which it is done. In Nigeria, FGC is seen as a rite of passage into womanhood and is considered vital to social cohesion and important for the tempering of female assertiveness and the enhancement of female passivity 1 . In Somalia, the practice of FGC is perpetuated because it is believed to protect a woman's virginity, increase fertility, and heighten male sexual pleasure 8,10,11 .…”
Section: Introductionmentioning
confidence: 99%